The Effect of Music Genre and Music-Preference Dimension on Acceptable Noise Levels in Listeners with ‘Normal’ Hearing - Gordon-Hickey, Susan; Bryan, Melinda F. (Journal of the American Academy of Audiology, 2022)
Background The acceptable noise level (ANL) is the maximum level of background noise that an individual is willing to accept while listening to speech. The type of background noise does not affect ANL results except for music.Purpose The purpose of this study was to determine if ANL differed due to music genre or music genre preference.Research Design A repeated-measures experimental design was employed.Study Sample Thirty-three young adults with normal hearing served as listeners.Data Collection and Analysis Most comfortable listening level and background noise level were measured to twelve-talker babble and five music samples from different genres: blues, classical, country, jazz, and rock. Additionally, music preference was evaluated via rank ordering of genre and by completion of the Short Test of Music Preference (STOMP) questionnaire.Results The ANL for music differed based on music genre; however, the difference was unrelated to music genre preference. Also, those with low ANLs tended to prefer the intense and rebellious music-preference dimension compared with those with high ANLs.Conclusions For instrumental music, ANL was lower for blues and rock music compared with classical, country, and jazz. The differences identified were not related to music genre preference; however, this finding may be related to the music-preference dimension of intense and rebellious music. Future work should evaluate the psychological variables that make up music-preference dimension to determine if these relate to our ANL.
Keywords: acceptable noise level; background noise; music preference